Tutok kargado - Ruiz, Jose Tence (Ateneo Art Gallery, 2008)
The accompanying catalog for the gathering of the socio-political art initiative, Tutok, in 2008, for a culminating show entitled 'Kargado', as a response to the current Filipino condition that has become alienated and indifferent under the throes of globalization and the zombification of a cyber-culture. The exhibition features 25 artists working in different media, which include Alfredo Esquillo, Karen Flores, Mark Salvatus, and Cesar Syjuco among others, alongside works from Ateneo's permanent collection, and is curated by Jose Tence Ruiz for the Ateneo Art Gallery.--Gallery website